2006
DOI: 10.1093/jac/dkl274
|View full text |Cite
|
Sign up to set email alerts
|

Rifampicin/imipenem combination in the treatment of carbapenem-resistant Acinetobacter baumannii infections

Abstract: The results of our study argue against the use of a rifampicin/imipenem combination for the treatment of carbapenem-resistant A. baumannii infections. However, combinations of rifampicin with other antibiotics merit further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 8 publications
2
55
1
Order By: Relevance
“…As rifampin was shown to be synergistic with CO or imipenem both in vitro and clinically, we enrolled rifampin as a third agent to try in combination. 1,17,24 The best results were obtained in the TIG-CO combination. Synergistic activity was found in 72% of the isolates with the TIG-CO combination, in 60% with the CO-RIF combination, and in only 12% with the TIG-RIF combination.…”
Section: Discussionmentioning
confidence: 98%
“…As rifampin was shown to be synergistic with CO or imipenem both in vitro and clinically, we enrolled rifampin as a third agent to try in combination. 1,17,24 The best results were obtained in the TIG-CO combination. Synergistic activity was found in 72% of the isolates with the TIG-CO combination, in 60% with the CO-RIF combination, and in only 12% with the TIG-RIF combination.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, rifampicin has been proposed as an alternative antimicrobial agent for the treatment of MDR A. baumannii, based on outcomes of in vitro studies 2,7,8 and in vivo infection models 12,27 . A previous study has shown that 64% of MDR A. baumannii were susceptible to rifampicin 7 .…”
Section: Discussionmentioning
confidence: 99%
“…One hundred A. baumannii isolates were collected from clinical specimens such as sputum (64), blood (12), urine (8), pus (from leg, 2; pleural empyema, 1; axilla, 2; vagina, 1; percutaneous endoscopic gastrostomy tube, 1; and eye, 1), body fluid (6) and tissue (2) from patients at Songklanagarind Hospital in Songkhla Province, Thailand during the JanuaryJuly 2010 period. Each isolate was collected from a different patient.…”
Section: Bacterial Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, studies have found conflicting results for the same antimicrobial combinations comparing animal in vivo studies with a follow-up clinical pilot study. 28,29 In this study, we performed time-kill analysis only for three different Acinetobacter species with similar MICs against various antimicrobial agents. The differences in the mechanisms of resistance seemed to result in different effective antibiotic combinations.…”
Section: Discussionmentioning
confidence: 99%